ANALISIS PENGARUH KUALITAS PELAYANAN DAN NILAI PELANGGAN TERHADAP KEPUASAN KONSUMEN PADA BALAI KESEHATAN PARU MASYARAKAT (BKPM) DI SEMARANG - Arhamni, Yolis; Khasanah, Imroatul (Diponegoro Journal of Management, 2015)
Need  of  healthy  become  one  of  important  need  of  people.  BKPM  (centre  ofcommunity lung health) is a community center that serves cheap healthy service for people in Semarang. As a service organization, satisfaction become main purpose of the service provider.This research is purposed to examine the impact of service quality and consumer value to patient satisfaction.The research is taken place at BKPM Semarang. The sample is 100respondents.Instrumentof questionnaire is used to collect the data. Regression analysis is applied to test the hypotheses of the research.Result  of  the  analysis  shows  that  service  quality  affect  positively  to  patient satisfaction. Patient that receives a better service will have higher satisfaction. Consumer value also affect positively to patient satisfaction.Patient that receives a more value from the service will have higher satisfaction.